Crustacea 2020
DOI: 10.5772/intechopen.88218
|View full text |Cite
|
Sign up to set email alerts
|

Scyllarid Lobster Biology and Ecology

Abstract: The family Scyllaridae is the most speciose and diverse of all families of marine lobsters. Slipper lobsters are found in both tropical and temperate habitats with hard or soft substrates and at different depths, and exhibit a wide array of morphological, anatomical, and physiological adaptations. Among the 20 genera and at least 89 species constituting 4 subfamilies, only some members of 4 genera, Thenus (Theninae), Scyllarides (Arctidinae), Ibacus and Parribacus (Ibacinae), form significant fisheries because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Scyllarides squammosus of the family Scyllaridae belongs to a taxon of slipper lobsters with four subfamilies, 88 species, and two subspecies (Wardiatno et al 2016) , previously thought to be 89 species (Yang et al 2012) . Although knowledge of S. squammosus has increased in recent years, scientific information is still limited and focused on only a few species (Lavalli and Spanier 2007;Lavalli et al 2020) , compared to the highly commercialized spiny lobsters of the Nephropidae and Palinuridae families (Spanier and Lavalli 2013) . This species can be distinguished by its last antennal segment, which is completely reduced to a flat plate and is used as a steering device to escape from predators (Wardiatno et al 2016) .…”
Section: Global Knowledge Of Scyllarides Squammosusmentioning
confidence: 99%
“…Scyllarides squammosus of the family Scyllaridae belongs to a taxon of slipper lobsters with four subfamilies, 88 species, and two subspecies (Wardiatno et al 2016) , previously thought to be 89 species (Yang et al 2012) . Although knowledge of S. squammosus has increased in recent years, scientific information is still limited and focused on only a few species (Lavalli and Spanier 2007;Lavalli et al 2020) , compared to the highly commercialized spiny lobsters of the Nephropidae and Palinuridae families (Spanier and Lavalli 2013) . This species can be distinguished by its last antennal segment, which is completely reduced to a flat plate and is used as a steering device to escape from predators (Wardiatno et al 2016) .…”
Section: Global Knowledge Of Scyllarides Squammosusmentioning
confidence: 99%
“…The first pereiopods of some decapod crustaceans become enlarged chelipeds that are used to manipulate food organisms and as weapons in predator avoidance and contest competition (Lee, 1995;Davie et al, 2015;Lavalli & Spanier, 2015). Decapod chelipeds show sexual dimorphisms; that is, they are generally larger in males than in females (Lee, 1995;Mariappan et al, 2000;Emlen, 2008).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The distribution of species of Thenus and other slipper lobsters (Scyllaridae) depends on several environmental factors (Spanier and Lavalli, 1998;Wardiatno et al, 2016), as observed in palinurids (Herrnkind et al, 1997;Butler et al, 2006). The nature of sediments and the depth of water are the 2 major factors that influence the abundance of slipper lobsters (Jones, 2007;Lavalli et al, 2019). The flathead lobster prefers soft, sandy sediment areas with medium-to-coarse particle size.…”
mentioning
confidence: 99%